Modification, Biological Evaluation and 3D QSAR Studies of Novel 2-(1,3-Diaryl- 4,5-Dihydro-1H-Pyrazol-5-yl)Phenol Derivatives as Inhibitors of B-Raf Kinase - Yang, Yu-Shun; Zhang, Fei; Tang, Dan-Jie; Yang, Yong-Hua; Zhu, Hai-Liang (PLOS ONE, 2014)
A series of novel 2-(1,3-diaryl- 4,5-dihydro-1H-pyrazol-5-yl)phenol derivatives (C1–C24) have been synthesized. The B-Raf inhibitory activity and anti-proliferation activity of these compounds have been tested. Compound C6 displayed the most potent biological activity against B-RafV600E (IC50 = 0.15 µM) and WM266.4 human melanoma cell line (GI50 = 1.75 µM), being comparable with the positive control (Vemurafenib and Erlotinib) and more potent than our previous best compounds. The docking simulation was performed to analyze the probable binding models and poses while the QSAR model was built to check the previous work as well as to introduce new directions. This work aimed at seeking more potent inhibitors as well as discussing some previous findings. As a result, the introduction of ortho-hydroxyl group on 4,5-dihydro-1H-pyrazole skeleton did reinforce the anti-tumor activity while enlarging the group on N-1 of pyrazoline was also helpful.